Use of fuzzy logic to produce a specific substrate for lettuce - Godinho, Emmanuel Zullo [UNESP]; Arruda, Amanda Alves [UNESP]; Caneppele, Fernando de Lima (My University, 2023)
Faced with the challenges of national horticulture, which needs to reduce production losses resulting from environmental problems, such as excessive rain, low temperatures, in addition to planting in soils considered poor, this work proposes to develop a Fuzzy set that can optimize the percentages of use in the production of a substrate with sand, earth and bovine organic compost. The Fuzzy model was elaborated based on experimental field data. For each variable, Fuzzy sets were assigned that characterized them along with their membership functions. The input variables were sand, earth and organic compost with a range of [0 to 40], in percentage and the output variable emergence speed index with a range of [0 to 2%]. The interpretation of the use of fuzzy logic in this experiment using real field data managed to optimize the best proportions of the use of sand, earth and organic compost for the production of a specific substrate for lettuce. Being used 20% for each raw material, obtaining 1% in the index of speed of emergence. This model developed with fuzzy logic allowed estimating the best conditions for the emergence speed index using sand, earth and organic compost for the germination and emergence of lettuce, since it can optimize the best proportions of use of raw materials, so that do not affect the external environment for the seed.
Utilização da lógica fuzzy para a produção de um substrato específico para a alface
Keywords: Earth; Fuzzy logic; Lactuca sativa; Organic compost; Sand